Mathematical Modeling on the Spread of Awareness Information to Infant Vaccination - Aminiel, Joram; Kajunguri, Damian; Mpolya, Emmanuel A. (Applied Mathematics, 2015)
In this paper, we examine the importance of spreading awareness information about infant vaccination in a population. A mathematical model for the spread of infant vaccination awareness information is proposed and analyzed quantitatively using the stability theory of the differential equations. The basic reproduction number 𝑅0 is obtained and its sensitivity analysis is carried out. The awareness free equilibrium is also proved to be locally and globally stable. Consideration is taken when 𝑅0 is greater than unity, which indicates that infant vaccination awareness information will invade the population and cause immunization to succeed. It is also proved that the maximum awareness equilibrium is locally stable if 𝑅0 is greater than unity. Numerical results show that word-of-mouth has a more impact on infant vaccination as compared to mass media, but better results are obtained by a combination of both word-of-mouth and mass media. For a successful infant vaccination programme, there is a need to emphasize both forms of awarenes.
Keywords: Awareness information; Infant vaccination